(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To evaluate the effect of “TLT-BCA” pills on inhibiting benign prostatic hyperplasia induced by testosterone propionate (TP) in Wistar rats. Subjects and methods: Wistar rats were injected subcutaneously with TP at a dose of 3mg/kg/24h or with sesame oil (physiological control group), and given “TLT-BCA” (treatment 1 and 2 groups), Dutasteride (reference group) or physiological saline (physiological control and pathological control groups) for 28 consecutive days. Results: “TLT-BCA” pills at dose 700mg/kg/24h and 2100mg/kg/24h reduced prostate weight, decreased MDA concentration in both blood and prostate tissue of rats (p < 0.01 compared to the pathology). Conclusions: “TLT-BCA” pills have reduced prostate weight on the model of benign prostatic hyperplasia in Wistar rats. The mechanism of action may be involved in the antioxidant effects.